On the reducibility of countable systems of linear difference equations - Samoilenko, A. M.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We solve the problem of reducibility of a countable linear system of standard difference equations with unbounded right-hand sides by the method of construction of iterations with accelerated convergence. For systems of this type with bounded right-hand sides, this problem is reduced to a finite-dimensional case.